Revisiting Indonesian Heritage in Elementary Education: Utilizing Critical Transformative Pedagogy to Foster Cultural Identity - Rosalina, Bunga (International Conference on Elementary Education, 2025)
This study examines the integration of cultural heritage in elementary education through a critical transformative pedagogical approach aimed at enhancing students' cultural identity. Through an in-depth literature review, the findings indicate that culturally-based teaching enriches students' academic experiences and significantly contributes to the formation of a strong cultural identity. The role of educators is crucial in the implementation of cultural education, linked to ongoing professional development and collaboration with the community. Moreover, the involvement of parents and local stakeholders in education reinforces cultural capital, which is essential for the success of culturally responsive education. This research underscores the importance of incorporating cultural content into the curriculum to prepare students to become active citizens in a multicultural society.